1999
DOI: 10.1002/(sici)1097-4628(19990103)71:1<75::aid-app10>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Transesterification in homogeneous poly(?-caprolactone)-epoxy blends

Abstract: Transesterification has been investigated in poly(-caprolactone) (PCL)-epoxy blends. In the hot melt process, the hydroxyl on diglycidyl ether of bisphenol-A (DGEBA) monomers is too low to give a noticeable transesterification reaction. In the postcure process, model reactions reveal that the hydroxyls from a ring-opening reaction are able to react with the esters of PCL. In the meantime, the PCL molecular weight decrease and its distribution becomes broader. Nuclear magnetic resonance spectra reveal that frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…[9][10][11] Although grafting reactions are not discussed in those studies, the occurrence of PCL grafting onto the crosslinked epoxy network is known to occur via (i) amidation of PCL with the amine curing agent, (ii) the hydroxyl end groups of PCL that react with the oxirane rings of the epoxy resin, and (iii) transesterification. 15,16 Similar changes in the crystallization behavior were observed after compatibilization of polymer blends by the addition of copolymers in the absence of crosslinking. Tang and Huang 12 reported an increase in T c for blends of PP and poly(ethylene oxide) (PEO) by compatibilization with a maleated PP-PEO copolymer, whereas Adewole et al 13 observed an increase in T c for PP in blends with poly (styrene) (PS) after the addition of a PP-PS graft copolymer.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…[9][10][11] Although grafting reactions are not discussed in those studies, the occurrence of PCL grafting onto the crosslinked epoxy network is known to occur via (i) amidation of PCL with the amine curing agent, (ii) the hydroxyl end groups of PCL that react with the oxirane rings of the epoxy resin, and (iii) transesterification. 15,16 Similar changes in the crystallization behavior were observed after compatibilization of polymer blends by the addition of copolymers in the absence of crosslinking. Tang and Huang 12 reported an increase in T c for blends of PP and poly(ethylene oxide) (PEO) by compatibilization with a maleated PP-PEO copolymer, whereas Adewole et al 13 observed an increase in T c for PP in blends with poly (styrene) (PS) after the addition of a PP-PS graft copolymer.…”
mentioning
confidence: 52%
“…Several studies on blends of poly(ε‐caprolactone) (PCL) with epoxy resins prepared via reaction‐induced phase separation (RIPS) showed a significant nucleating effect of the dispersed, amorphous epoxy phase on the PCL matrix 9–11. Although grafting reactions are not discussed in those studies, the occurrence of PCL grafting onto the crosslinked epoxy network is known to occur via (i) amidation of PCL with the amine curing agent, (ii) the hydroxyl end groups of PCL that react with the oxirane rings of the epoxy resin, and (iii) transesterification 15, 16. Similar changes in the crystallization behavior were observed after compatibilization of polymer blends by the addition of copolymers in the absence of crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…It is known, for example, that PCL becomes immiscible with certain anhydride-cured epoxy resins during polymerization, but typically remains fully miscible with amine-cured epoxy resins up to full conversion of these latter. This difference in miscibility is attributed to the presence of hydroxyl groups in the amine-cured epoxy, which are capable of forming hydrogen bonds with the ester groups of the PCL [11,12]. PIPS has nevertheless been observed in epoxy-PCL blends cured with the diamines diethyltoluenediamine (DETDA) and 4,4 0 -diaminodiphenyl sulfone (DDS), and the dependence of the morphology of DDS-cured epoxy-PCL blends on composition and cure temperature has been described in some detail by Chen and Chang [13,14].…”
Section: Introductionmentioning
confidence: 76%
“…Thermoplastics that have been demonstrated to show this type of morphology when combined with epoxy thermoset resins include polycaprolactone (PCL) [5,[11][12][13][14][15][16][17][18][19][20], poly (ether sulfone) [21][22][23], polyetherimide [24][25][26][27], poly(methyl methacrylate) [28][29][30] and polystyrene [28][29][30]. The potential of PCL for the thermal healing of epoxies stems from its low melting temperature (55°C) and high degree of thermal expansion (an increase in volume by up to 14% between room temperature and 150°C [31]), and it has also been demonstrated to be of interest for shape-memory assisted self-healing [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In both studied cases, RIPS occurs, so two different phases can be seen: one corresponding to the rich-PCL phase and the other one to the epoxy matrix. There are numerous PCL/TS systems that prove totally miscible blends, forming inter-penetrating network (IPN), without phase separation [18,19]. This is explained because of the pendant hydroxyl groups, resulted from the oxirane ring opening reaction with the amine curing agent, which play an important role because they form hydrogen-bonds with PCL, enhancing its solubility into the epoxy network.…”
Section: Characterizationmentioning
confidence: 99%